In Situ Radiographic Investigation of (De)Lithiation Mechanisms in a Tin‐Electrode Lithium‐Ion Battery. Issue 9 (14th April 2016) - Sun, Fu; Markötter, Henning; Zhou, Dong; Alrwashdeh, Saad Sabe Sulaiman; Hilger, Andre; Kardjilov, Nikolay; Manke, Ingo; Banhart, John
Abstract: The lithiation and delithiation mechanisms of multiple‐Sn particles in a customized flat radiography cell were investigated by in situ synchrotron radiography. For the first time, four (de)lithiation phenomena in a Sn‐electrode battery system are highlighted: 1) the (de)lithiation behavior varies between different Sn particles, 2) the time required to lithiate individual Sn particles is markedly different from the time needed to discharge the complete battery, 3) electrochemical deactivation of originally electrochemically active particles is reported, and 4) a change of electrochemical behavior of individual particles during cycling is found and explained by dynamic changes of (de)lithiation pathways amongst particles within the electrode. These unexpected findings fundamentaly expand the understanding of the underlying (de)lithiation mechanisms inside commercial lithium‐ion batteries (LIBs) and would open new design principles for high‐performance next‐generation LIBs. Abstract : Lithiation close up : A radiography cell is designed and manufactured for in situ investigation of the underlying (de)lithiation mechanisms in a Sn/C‐composite electrode. Four (de)lithiation phenomena are highlighted: 1) an inhomogeneous electrochemical (de)lithiation, 2) a varying individual lithiation time versus whole cell discharge time, 3) an electrochemical deactivation, and 4) a dynamic (de)lithiation pathway.